The impact of customers interaction on social media towards brand awareness among students UiTM Cawangan Melaka Kampus Alor Gajah / Nurul Afifah Aniqah Johari - Johari, Nurul Afifah Aniqah (Faculty of Business and Management, 2020)
This study examines on Customers Interaction and Brand Awareness. The results were collected from 346 respondents through a questionnaire. A survey consists of 27 questions that use a Likert Scale questions to establish measurable values from the respondents. The data analysis intends to determine whether there are significant impact between the independent variables (Purchase Intention, Word of Mouth, Customer Attitude and Brand Page Commitment) with the dependent variable (Brand Awareness). This study found that there were only three from the independent variables (Word of Mouth, Customer Attitude and Brand Page Commitment) has significant effect where by only one independent variable (Purchase Intention) has insignificant effect with the dependent variable (Brand Awareness). The data has been analyzed by using SPSS software.